2013
DOI: 10.1128/aem.02728-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Leptospira Strains Isolated from Environmental Soil and Water in the Philippines and Japan

Abstract: There have been few reports on the epidemiological analysis of environmental Leptospira isolates. This is probably because the isolation of leptospires from the environment was usually unsuccessful due to the overgrowth of contaminants and the slow growth of Leptospira. In this study, we collected a total of 88 samples of soil and water from three sites: Metro Manila and Nueva Ecija, Philippines (an area where Leptospira is now endemic), and Fukuoka, Japan (an area where Leptospira was once endemic). We succee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
129
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(142 citation statements)
references
References 15 publications
7
129
1
5
Order By: Relevance
“…The gene sequence for 16S rDNA was extracted from the complete genome and compared to 108 16S rDNA sequences available for Leptospira from the Ribosomal Database project (https://rdp.cme.msu.edu/). Phylogenetic analysis indicated that GWTS isolate #1 clustered among 4 strains of Leptospira recently isolated from soil samples in Fukuoka, Japan (designated as MS267, MS306, MS311, and MS316 respectively[48]), Fig 1 and S1 Fig. These, in turn, cluster most closely with Leptospira genomospecies 1, which has recently been renamed L .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The gene sequence for 16S rDNA was extracted from the complete genome and compared to 108 16S rDNA sequences available for Leptospira from the Ribosomal Database project (https://rdp.cme.msu.edu/). Phylogenetic analysis indicated that GWTS isolate #1 clustered among 4 strains of Leptospira recently isolated from soil samples in Fukuoka, Japan (designated as MS267, MS306, MS311, and MS316 respectively[48]), Fig 1 and S1 Fig. These, in turn, cluster most closely with Leptospira genomospecies 1, which has recently been renamed L .…”
Section: Resultsmentioning
confidence: 99%
“…Prior isolates of L . alstonii are derived from the amphibians Bombina orientalis and Rana nigromaculata , which belong to Neobatrachia species in China, or are derived from soil samples in Japan or Malaysia [48, 55, 59]. Whether L .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 5 isolates (5 17, 29 ) were found to be closely related to L. alstonii with 99 to 100 identity, whereas 1 isolate (1 17, 6 ) is closely related to L. kmetyi, with 99 identity. The presence of L. alstonii and L. kmetyi in the environment has been reported in many countries (7)(8)(9)(10). Recently, L. alstonii was isolated from greater white toothed-shrews in Ireland (11) and from an asymptomatic cow in a slaughter house in Brazil (12).…”
Section: Discussionmentioning
confidence: 99%
“…L. fainei was successively cultured from two human patients with Weil's disease and antibody titers have been found in sera from cattle in Australia, France and Indonesia ( Chappel et al, 1996;Petersen et al, 2001). L. wolffii was identified as a potential pathogenic species, detected in infected humans, in sheep sera and dogs urine and can be potentially pathogenic to human and probably animal hosts (Zakeri et al, 2010); and L. licerasiae causes mild disease in humans and has been isolated from peridomestic and wild rodents and marsupials in Peruvian Amazon (Matthias et al, 2008;Ricaldi et al, 2012) and from environmental water (Saito et al, 2013). Krull et al (2015) showed that early BDD lesions had minimal populations of Treponema spp.…”
Section: Discussionmentioning
confidence: 99%